Clinical Resolution of Osmotic Demyelination Syndrome following Overcorrection of Severe Hyponatremia - Ruhin Yuridullah; Vinod Kumar; Sushant Nanavati; Monisha Singhal; Chandra Chandran (Case Reports in Nephrology)
Osmotic Demyelination Syndrome (ODS) occurs after rapid overcorrection of severe chronic hyponatremia usually in those with a predisposition such as chronic alcoholism, malnutrition, or liver disease. Rarely, do patients make a full recovery. We report a case of ODS secondary to overcorrection of severe hyponatremia with pathognomonic clinical and radiologic signs making a complete neurological recovery. A detailed course of events, review of literature, and optimal and aggressive management strategies are discussed. There is some controversy in the literature regarding the prognosis of these patients. Our aim here is to show that, with aggressive therapy and long-term care, recovery is possible in these patients.